(untitled) (International Online Journal of Language, Communication, and Humanities (INSANIAH), 2023)
The study examined the reasons for casualisation of labour at the Cement Company of Northern Nigeria, Sokoto. The objective of the study was to examine the reasons for casualisation of labour in CCNN. Neoliberal theory was used as theoretical guide. Qualitative method of data collection was employed using focus group discussion and key informant interview as instruments of data collection. Sixty-eight casual workers and three management staff were purposively selected. The data were analysed using content analyses. The data revealed that unemployment, drive to cut down cost and maximize profits were some of the reasons for casualization in CCNN. The study recommends more efforts should be put in place by governments to create job opportunities for youths and other labour force and government policies relating to the period of time in which one can serve as a casual worker in any organization should be enforced by appropriate government agencies.